Global Maya : Work and Ideology in Rural Guatemala - Goldin, Liliana R. (UPCC book collections on Project Muse., 2009)
In the central highland Maya communities of Guatemala, the demands of the global economy have become a way of life. This book explores how rural peoples experience economic and cultural change as their country joins the global market, focusing on their thoughts about work and sustenance as a way of learning about Guatemala's changing economy.